Categorization of questions posed before and after inquiry-based learning (2014)
Posing research questions is the central ability of the scientific thought. This article examines the ability of sixth grade children to pose researchable questions before and after a three months’ work on a didactic sequence based on the inquiry school model. According to their purpose, the questions asked by children, after reading a text, were classified into researchable questions -susceptible to be empirically explored-, questions about a cause, and questions on a piece of data. The results show that the amount and the type of questions the students were able to pose during the intervention changed, from most of questions on data or information, to most of researchable questions, subsequently, the importance of designing teaching approaches to foster this ability was proved.